Trends and challenges of smart facades technologies in buildings and the reality of their application in Saudi Arabia (Riyadh as a model) اتجاهات وتحدیات تقنیات الواجهات الذکیة بالمبانی وواقع تطبیقها بالمملکة العربیة السعودیة (مدینة الریاض نموذجاً) - MUTEB ALAYAFI; Ahmed Mostafa (JES: Journal of Engineering Sciences, 2022)
The technical and technological development in the architecture sector contributes to reducing the consumption of primary energy resources, by employing them in the architecture sector, especially in the architectural facades. It produced smart facades that respond to the surrounding environment and its changes to maintain the stability of the internal environment while benefiting from renewable natural energy. Unlike the traditional facades, which were highly stable and contributed to raising the consumption of electrical energy in buildings, their consumption in buildings to provide the appropriate internal environment for users amounted to approximately 60% of the total energy consumed in the buildings sector. With Saudi Arabia heading within its 2030 vision to digital transformation and support for the application of the latest technologies in all fields. The problem of the lack of sufficient data for the reality of the availability and application of these technologies in the Saudi local market and what are the most important trends and challenges facing their application. This data represents an important resource to support the decision-maker in prioritizing, directing support, overcoming the challenges it faces, and benefiting from its capabilities in achieving user convenience and operating sustainability at the same time, Which is considered a research gap that represented the main motivation for this research, which aims to extract the most important trends of smart facades applications and technologies, the challenges facing their application, and the reality of the availability and application of these technologies in Riyadh in Saudi Arabia as an initiative for future studies to bridge this research gap in this important field. The research used the descriptive analytical method to achieve its objectives in two parts: the first was the literature reviews that dealt with the trends and challenges of applications and technologies of smart facades, and the second was the monitoring of the reality of the availability and application of these technologies. This research paper constitutes an initiative aimed at "bridging the research gap" occurring in the local market in the Saudi Arabia to document the most important trends and challenges facing the field of smart facades technologies, and to encourage future studies in this direction on the one hand, and to monitor the relative importance of these trends and challenges and the reality of their availability and application on the one hand. Second, in addition to being considered one of the digital transformation initiatives of the 2030 vision from a third party. یساهم التطور التقنی والتکنولوجی بقطاع العمارة فی خفض استنزاف الموارد الأولیة للطاقة، بتوظیفها بقطاع العمارة وعلى وجه الخصوص بواجهاتها، فتشکلت واجهات ذکیة تستجیب للبیئة المحیطة ومتغیراتها لتحافظ على استقرار البیئة الداخلیة بالإضافة الى انها استغلت تلک التقنیات للاستفادة من الطاقة الطبیعیة المتجددة، بخلاف الواجهات التقلیدیة التی کانت ثابته الى حد کبیر وتساهم فی زیادة الاستهلاک للطاقة الکهربائیة بالمبانی حیث بلغ استهلاک الطاقة الکهربائیة فی المبانی لتوفیر البیئة الداخلیة المناسبة للمستخدمین بما یقارب 60% من اجمالی الطاقة المستهلکة فی قطاع المبانی. ومع توجه المملکة إلى التحول الرقمی ودعم تطبیق أحدث التقنیات فی جمیع المجالات ضمن رؤیتها 2030، تظهر إشکالیة عدم توافر بیانات کافیة لواقع اتاحة وتطبیق هذه التقنیات فی المملکة فی السوق المحلی وأهم اتجاهاتها والتحدیات التی تواجه تطبیقها. تمثل هذه البیانات مورداً مهماً لدعم متخذ القرار فی تحدید الأولویات وتوجیه الدعم اللازم لتحقیق فعالیة تطبیقها، والتغلب على التحدیات التی تواجهها، والإستفادة من إمکانیاتها فی تحقیق راحة المستخدم واستدامة التشغیل فی نفس الوقت، وهو ما یعتبر فجوة بحثیة مثلت الحافز والدافع الرئیسی لهذا البحث الذی یهدف إلى استخلاص أهم توجهات تطبیقات وتقنیات الواجهات الذکیة، والتحدیات التی تواجه تطبیقها، وواقع اتاحة هذه التقنیات وتطبیقها فی مدینة الریاض بالمملکة العربیة السعودیة کمبادرة لدراسات مستقبلیة لتجسیر هذه الفجوة البحثیة لهذا المجال المهم. تبنى البحث المنهج الوصفی التحلیلی لتحقیق أهدافه على جزأین: الأول تم فیه المراجعات الأدبیة التی تناولت اتجاهات وتحدیات تطبیقات وتقنیات الواجهات الذکیة، والثانی تم فیه رصد واقع اتاحة وتطبیق هذه التقنیات من جهة أخرى. تشکل هذه الورقة البحثیة مبادرة تهدف إلى "تجسیر الفجوة البحثیة" الحادثة فی السوق المحلی بالمملکة العربیة السعودیة